Characterization of Woodceramics Prepared from Liquefied Corncob and Poplar Powder - Sun, De-Lin; Yu, Xian-Chun; Wang, Rong (Asian Journal of Chemistry, 2012)
A woodceramics is prepared from liquefied corncob and poplar powder. The basic property of this material is closely correlated to the carbonization temperature and liquefied corncob content. The thermogravimetric analysis indicates that the high liquefied corncob content can decrease weight loss. X-ray diffraction analysis shows that higher carbonization temperature can improve the graphitization degree of this material, but the phase composition is not mainly related to the liquified corncob content. Scanning electron microscopy confirms that the poplar powder is as a natural plant template and the pore of woodceramics partly keeps the native characteristics of the wood with size ranging from 5 to 20 μm. It is porous carbon material with three-dimensional network structure.